Significance of Bottom-Up Approach for Policy Implementation (PAAN Journal, 2024)
Developing the connection between the creation and execution of policies is the primary goal of the top-down approach. The ability to be innovative, experienced, knowledgeable, and authoritative allows top level personnel to oversee lower level policy implementation. However, there are certain drawbacks to the top-down strategy. At the top, things like local conditions, surroundings, and ground reality are unknown. A bottom-up strategy was developed to lessen the constraints of the top-down strategy when implementing policies. As a result, the emphasis on a bottom-up approach, the significance of street-level bureaucrats, and locally based organizations can all contribute to the implementation of policies successfully.